Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 2415182 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "DatasetKey is Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014" ] } The dataset includes 2415182 records from 1 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0005507-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences